ChemInform Abstract: Site‐Selective Addition of Maleimide to Indole at the C‐2 Position: Ru(II)‐Catalyzed C—H Activation. Issue 9 (February 2016) - Lanke, Veeranjaneyulu; Bettadapur, Kiran R.; Prabhu, Kandikere Ramaiah
Abstract: The scope of the title reaction is broadened towards pyrrole (IV) and maleates (VIII) as substrates.